2016
DOI: 10.1111/efp.12252
|View full text |Cite
|
Sign up to set email alerts
|

Variations in virulence and hyphal growth of four Raffaelea quercivora isolates within Quercus crispula

Abstract: Mass mortality of fagaceous trees caused by Japanese oak wilt has occurred widely in Japan. Although virulence of the causal fungus, Raffaelea quercivora, appeared to differ among isolates, its relation to the fungal growth within trees was unknown. To clarify the differences in fungal virulence against susceptible Quercus crispula, we examined fungal growth of four R. quercivora isolates within trees and the resulting virulence. In our study, the isolates were multiple-inoculated in seedlings and single-inocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…quercivora collected from 13 host species growing in 14 prefectures in areas affected by JOW in Japan (Figure 1, Table S1). Except for isolates whose virulence had been evaluated in previous studies (Kusumoto et al, 2015; Torii et al, 2016) and the type strain of R . quercivora , all isolates were identified as R .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…quercivora collected from 13 host species growing in 14 prefectures in areas affected by JOW in Japan (Figure 1, Table S1). Except for isolates whose virulence had been evaluated in previous studies (Kusumoto et al, 2015; Torii et al, 2016) and the type strain of R . quercivora , all isolates were identified as R .…”
Section: Methodsmentioning
confidence: 99%
“…10 mm and inserted a fungus‐colonized toothpick (5 mm length, 1.5 mm diameter) into the hole. We chose 9 of the 40 isolates that originated from different geographical regions and displayed variation in virulence in prior studies (Kusumoto et al, 2015; Torii et al, 2016). To minimize variation in host defence responses between individual trees, we used 10 twigs of the same tree for all 9 isolates and the control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In both tests, inocula were prepared by culturing wooden sticks with or without the fungus as described by Torii et al. () except for using the fungal isolate RA2117, which was preserved in the Laboratory of Forest Pathology and Mycology, Mie University. In Experiment 1, eight seedlings of each species were inoculated on 9 July 2012.…”
Section: Methodsmentioning
confidence: 99%
“…() detected most hyphae in non‐conductive sapwood under both artificial and natural conditions. Moreover, Torii, Matsuda, and Ito (), Torii, Ito, Nagao, Matsuda, and Ito () suggested that the extent of mycelial colonization was proportional to the amount of non‐conductive sapwood.…”
Section: Introductionmentioning
confidence: 99%